Experimental studies on soft contact lenses for controlled ocular delivery of pirfinedone: in vitro and in vivo. (21st November 2016) - Yang, Mei; Yang, Yangfan; Lei, Ming; Ye, Chengtian; Zhao, Chunshun; Xu, Jiangang; Wu, Kaili; Yu, Minbin
Abstract: Context : Pirfinedone (PFD) is a novel agent which has the potential to prevent scarring in the eyes. The 0.5% PFD eye drops exhibits poor bioavailability. Whereas, the feasibility of using contact lens as ocular drug delivery device initiated novel possibilities. Objective : To evaluate the delivery of PFD by soft contact lens (SCL) in vivo, we screened the most suitable lens material for PFD among various commercially available SCL materials in vitro . Material and methods : Firstly, 11 different SCLs (−1.00 diopter) were respectively soaked in 2 ml of 0.05% PFD-loading solution for 24 h to fully absorb drug, and then placed in fresh phosphate buffered saline (PBS) to release the drug. PFD concentration in PBS was determined by ultraviolet absorbance at 310 nm. Secondly, by immersing in 2 ml of 0.5% PFD eye drops for 24 h, the polymacon lens (0.00 diopter) was then placed on the cornea of New Zealand rabbits. PFD concentrations were detected by high performance liquid chromatography (HPLC) in tears, aqueous humor, conjunctiva, cornea, and sclera at different time points. Results : PFD showed some affinity for pHEMA-based lenses and the polymacon lens more slowly released more amount of PFD than any other lens in vitro ( p < 0.001). Compared with eye drops, drug-loaded SCLs greatly enhanced the retention time and concentrations of PFD in cornea and aqueous humor and consequently improved the bioavailability of PFD. Conclusion : Polymacon-based SCL is probably a promising vehicle to be an effective ophthalmic delivery system for PFD.